Changing trends in genital cancer - Singh, Abha; Kujur, Avinashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Globally, cancers in all forms are causing about 12% of all deaths. In developed countries cancer is the second leading cause of death accounting for 21% of mortality by other causes and in developing countries it ranks third, accounting for 9.5% of all deaths. The objective was to find the incidence of genital malignancy and any change in the trend at Pandit Jawahar Lal Nehru Memorial Medical College, Raipur, Chhattisgarh, India. Methods: This was a cross-sectional, retrospective, observational study conducted in Dr. BRAM Hospital, Department of Obstetrics and Gynecology from 2000 to 2015. We analyzed data for demographic profile, type of the genital carcinoma and the stages in which they reported and observed any changing trends. Results: Over 15 years the contribution of genital cancer remained almost stable at 2.78% in 2000 to 2.48% in 2015. 85% women belonged to rural residence, 75% were educated up to high school level and 76% women were from low socioeconomic status. Maximum prevalence of genital cancer is 65.90% falls in 45-60 years age group. Young age at first sexual activity, low education, parity >4 were found to be associated risk factors. Most significant changing trend was that the incidence of cancer cervix decreased by 11%. There was a shift from stage III to stage II at the time of reporting. The cancer endometrium emerged as new site for genital cancer with increased incidence. Conclusions: Cervical cancers are the most common cause of mortality but it is a preventable disease. Its decreasing trend and shift to early stage diagnosis is a positive beginning.